The role of a proposed motor program in the development of some motor abilities for children with simple mental retardation Field study at the Pedagogical Psychological Center in DJELFA - NADJEM, KHALED (sports creativity, 2025)
This study aimed at developing some of the motor abilities of children with mild mental retardation through a modified motor program that was tested on the research sample within the pedagogical psychological center in The Eyelid, where the sample was selected In a deliberate way, the sample included 18 children with mild mental retardation, divided into two controlled and experimental groups, and we followed the experimental method to suit the research. We did tribal measurements of the two groups and after applying the program and the dimensional measurements show that there are statistically significant differences between the control and experimental groups, and one of the most important results was that the proposed motor program has a the development elements of motor abilities